Effects of shoe collar height and limb dominance on landing knee biomechanics in female collegiate volleyball players - Legg, L.; Donahue, T.; Peel, S.; Piland, S.; Thorsen, T. (Journal of Sports Sciences, 2024)
Volleyball-specific footwear with higher collar heights (a mid-cut shoe) are worn to restrict ankle motion. Reduced ankle dorsiflexion has been associated with increased frontal plane motion and injury risk at the knee. With the high frequency of unilateral landings in volleyball, the purpose of this study was to determine the effect of volleyball-specific shoes and limb dominance on knee landing mechanics in collegiate volleyball players. It was hypothesized that participants would exhibit smaller sagittal plane and greater frontal plane knee joint mechanics in mid-cut and dominant limb and that vertical and posterior directed ground reaction forces would be greater wearing mid-cut, yet similar between limbs. Seventeen female volleyball players performed unilateral landings on each limb in mid-cut and low-top volleyball shoes. For shoe main effects, smaller peak dorsiflexion angle and internal peak plantarflexion moment and greater peak medial ground reaction force were found in the mid-cut but with no impact on knee mechanics. For limb main effects, the internal peak knee abduction moment was greater in the dominant limb. Greater peak lateral ground reaction force was found in the interaction between the non-dominant limb and low-top. Further research is warranted to better understand shoe and limb impact in volleyball players.